2009
DOI: 10.2174/1874620900902010011
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Relation between Obstructive Sleep Apnea and Diabetic Macular Edema Associated with Optic Nerve Fiber Layer Infarcts

Abstract: Abstract:Purpose: To describe a possible relationship in obese diabetics between obstructive sleep apnea syndrome (OSAS) and ischemic retinopathy with diffuse macular edema.Design: Prospective, observational case series. Methods:Obese diabetics (n=22) in a retina clinic who admitted to symptoms of sleep apnea on survey were compared with a cohort of 22 similarly obese diabetic patients.Complete ocular examination, fundus photography, fluorescein angiography,overnight polysomnography, blood pressure measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, impaired antioxidant defense systems including reduced enzymes such as catalase and glutathione peroxidase and superoxide dismutase, also lead to generation of retinal ROS/RNS that are exacerbated by variations in tissue exposure to glucose (52,53). Considering these conditions, it is not surprising that sleep apnea, with hypoxic episodes that result in retinal vessel dilation and hyperperfusion but are followed by reactive acute hypertensive reprise, are associated with severe exacerbation in the prevalence of diabetic retinopathy (54,55).…”
Section: Rosmentioning
confidence: 99%
“…Furthermore, impaired antioxidant defense systems including reduced enzymes such as catalase and glutathione peroxidase and superoxide dismutase, also lead to generation of retinal ROS/RNS that are exacerbated by variations in tissue exposure to glucose (52,53). Considering these conditions, it is not surprising that sleep apnea, with hypoxic episodes that result in retinal vessel dilation and hyperperfusion but are followed by reactive acute hypertensive reprise, are associated with severe exacerbation in the prevalence of diabetic retinopathy (54,55).…”
Section: Rosmentioning
confidence: 99%
“…These studies, and four of the six studies that reported non‐adjusted ORs, reported no significant association between OSA and DR . Only two small studies from the USA ( n = 142) , in which no adjustments for potential confounders were made, reported significant associations; however, these unadjusted models were likely to be exposed to multiple confounders such as gender and BMI, therefore, overall, there was no convincing evidence that OSA was associated with DR in their Type 2 diabetes population.…”
Section: Resultsmentioning
confidence: 92%
“…The definition of DR was variable, and in six studies no clear definition was provided . Definitions included use of diagnosed DR through the English National Screening Program for Diabetic Retinopathy , or from medical records .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations